2016
DOI: 10.4274/tjh.2015.0259
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Tumor Lysis Syndrome in Chronic Lymphocytic Leukemia

Abstract: Tumor lysis syndrome (TLS) is an important oncological emergency that is usually observed with hematological malignancies and rarely with solid tumors. It can be induced either by therapy or spontaneously. Radiotherapy-induced TLS has been rarely reported in the literature. Here we present a patient with a diagnosis of metastatic prostate cancer and chronic lymphocytic leukemia complicated with TLS during palliative radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…However, corticosteroids, radiation, hormonal agents, or antibodies may also cause a significant TLS. 22 24 Less frequent, spontaneous TLS can develop prior to initiation of anticancer therapy. 11 , 13 , 25 , 26 Even invasive procedure like biopsies, 16 embolization, 27 , 28 and tumor surgery 29 could lead to TLS.…”
Section: Incidencementioning
confidence: 99%
“…However, corticosteroids, radiation, hormonal agents, or antibodies may also cause a significant TLS. 22 24 Less frequent, spontaneous TLS can develop prior to initiation of anticancer therapy. 11 , 13 , 25 , 26 Even invasive procedure like biopsies, 16 embolization, 27 , 28 and tumor surgery 29 could lead to TLS.…”
Section: Incidencementioning
confidence: 99%
“…In addition, previous studies have also focused on the effects of the exposure to non-ionizing radiofrequencies on brain tumors, leukemia, salivary gland tumors, infertility and electro-hypersensitivity ( 3 , 6 , 19 , 20 ). Although a number of studies have investigated the association between exposure to radiation and cancer, the majority of meta-analysis studies have focused on the association between mobile phones and tumors ( 21-23 ) or electromagnetic fields and breast cancer ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table II shows the available reports on RT-induced TLS (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Two studies reported three cases of RT-induced TLS in MM (19,20).…”
Section: Discussionmentioning
confidence: 99%